2012
DOI: 10.1002/jbmr.1624
|View full text |Cite
|
Sign up to set email alerts
|

Compromised trabecular microarchitecture and lower finite element estimates of radius and tibia bone strength in adults with turner syndrome: A cross-sectional study using high-resolution–pQCT

Abstract: Although bone mass appear ample for bone size in Turner syndrome (TS), epidemiological studies have reported an increased risk of fracture in TS. We used high-resolution peripheral quantitative computed tomography (HR-pQCT) to measure standard morphological parameters of bone geometry and microarchitecture, as well as estimated bone strength by finite element analysis (FEA) to assess bone characteristics beyond bone mineral density (BMD) that possibly contribute to the increased risk of fracture. Thirty-two TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Their BMD may appear falsely reduced when evaluated by DXA due to the small bone size accompanying short stature and the differences in bone geometry due to SHOX deficiency (427). Furthermore, quantitative CT (QCT) evaluation of BMD has shown normal trabecular bone density (428) with falsely reduced cortical bone mineral content due to the partial volume effect (429), while high-resolution peripheral QCT has shown compromised microarchitecture and lower bone strength in both the tibia and radius (430). Therefore, radiographic evaluation of BMD may be difficult to interpret.…”
Section: Osteopenia Fracture Risk and Vitamin D Therapymentioning
confidence: 99%
“…Their BMD may appear falsely reduced when evaluated by DXA due to the small bone size accompanying short stature and the differences in bone geometry due to SHOX deficiency (427). Furthermore, quantitative CT (QCT) evaluation of BMD has shown normal trabecular bone density (428) with falsely reduced cortical bone mineral content due to the partial volume effect (429), while high-resolution peripheral QCT has shown compromised microarchitecture and lower bone strength in both the tibia and radius (430). Therefore, radiographic evaluation of BMD may be difficult to interpret.…”
Section: Osteopenia Fracture Risk and Vitamin D Therapymentioning
confidence: 99%
“…After correcting for size differences between groups, the percentage of women with TS classified as osteoporotic via DXA dropped from 20 to 5 % [15]. Literature suggests TS subjects have lower aBMD, compromised cortical [16][17][18] and trabecular [7] bone as well as lower estimates of bones strength [7] compared with control groups. The effects of GH on volumetric bone density and bone micro-architecture remain unclear.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, methods such as finite element (FE) analysis provide a subject-specific bone strength estimate [6]. One study using HR-pQCT of TS subjects has been performed [7] identifying micro-architectural deficits; however, the authors did not assess whether GH treatment influences those changes.…”
Section: Introductionmentioning
confidence: 98%
“…23 Also, the studies that used pQCT, a method which is able to independently provide measurements of 3-dimensional bone density and an assessment of trabecular and cortical bone density, have revealed significantly reduced cortical volumetric BMD (vBMD) and cortical thickness at some sites, and lower bone strength. [20][21][22] Holroyd et al showed by this method not only a significant reduction in cortical vBMD at the proximal radius, but in cortical thickness as well (Z-score of −2.58 and −2.89, respectively). 9 Moreover, they found no differences in the total vBMD Z-score or the trabecular vBMD Z-score at the distal radius.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of studies indicate that the abnormalities seem to be only in cortical bone, some studies show compromised trabecular microarchitecture in patients with TS. 20,21 However, reduced cortical BMD in young TS patients is not proven to lead to increased fractures. [22][23][24] We assessed the skeletal status of a group of young females with TS at 2 different skeletal sites using 2 different densitometric techniques.…”
Section: Discussionmentioning
confidence: 99%